2006
DOI: 10.1182/blood-2006-04-019034
|View full text |Cite
|
Sign up to set email alerts
|

RhoH is important for positive thymocyte selection and T-cell receptor signaling

Abstract: RhoH is a small GTPase expressed only in the hematopoietic system. With the use of mice with targeted disruption of the RhoH gene, we demonstrated that RhoH is crucial for thymocyte maturation during DN3 to DN4 transition and during positive selection. Furthermore, the differentiation and expansion of DN3 and DN4 thymocytes in vitro were severely impaired. These defects corresponded to defective TCR signaling. Although RhoH is not required for TCR-induced activation of ZAP70 and ZAP70-mediated activation of p3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 35 publications
4
103
0
Order By: Relevance
“…These binding proteins may also participate in signal transduction. Among such binding proteins, we identified RhoH, a member of the Rho family of small GTPases that is known to be expressed in hematopoietic cells [31]. Overexpression of RhoH potentiated the effect of BCR stimulation on the overall level of protein tyrosine-phosphorylation in Namalwa cells (Figs.…”
Section: Identification Of Rhoh As a Binding Partner For Phosphorylatmentioning
confidence: 96%
“…These binding proteins may also participate in signal transduction. Among such binding proteins, we identified RhoH, a member of the Rho family of small GTPases that is known to be expressed in hematopoietic cells [31]. Overexpression of RhoH potentiated the effect of BCR stimulation on the overall level of protein tyrosine-phosphorylation in Namalwa cells (Figs.…”
Section: Identification Of Rhoh As a Binding Partner For Phosphorylatmentioning
confidence: 96%
“…In contrast, little is known about the function of the many other members of the Rho family, such as RhoH/TTF. Recently published work suggests that RhoH/TTF plays a key role in TCR signaling (13,30). For instance, it has been demonstrated that RhoH/TTF is required for recruitment of ZAP70 to the TCR.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ/Ϫ mice were generated and provided by Dr. C. Brakebusch (Department of Molecular Pathology, University of Copenhagen, Copenhagen, Denmark) (13). For all experiments, 6-to 8-wk-old mice with a C57BL/6J background were used.…”
Section: Mice Rhohmentioning
confidence: 99%
“…A role for RhoH downstream of CXCR4 signaling is identified by a failure to activate PAK1 in response to strong stimulation via CXCR4 in the absence of RhoH (13), further linking RhoH with regulation of the cytoskeleton by Rac GTPases. However, constitutive activation of Rac1 increases proliferation of thymocytes in DN3 and an accelerated transition from DN3 to DN4 (20), whereas RhoH-deficient cells reveal diminished signaling and a block at this stage even in the presence of activated Rac1 (21), suggesting that regulation by RhoH is more complicated than only cytoskeletal effects. Defects in thymic selection, alongside studies of proximal TCR signals implicate RhoH as an important player in conjunction with Zap70 (9,21).…”
Section: Discussionmentioning
confidence: 96%
“…However, constitutive activation of Rac1 increases proliferation of thymocytes in DN3 and an accelerated transition from DN3 to DN4 (20), whereas RhoH-deficient cells reveal diminished signaling and a block at this stage even in the presence of activated Rac1 (21), suggesting that regulation by RhoH is more complicated than only cytoskeletal effects. Defects in thymic selection, alongside studies of proximal TCR signals implicate RhoH as an important player in conjunction with Zap70 (9,21). Zap70 is also reported to be involved in outside-in signaling for high-affinity LFA-1-mediated adhesion (22).…”
Section: Discussionmentioning
confidence: 96%